Representation of Human Violence Against Nature in Ted Hughes’ Selected Poems - Eva Najma; Febrianti Syafitri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2022)
The existence of nature-themed literary work is not only used as a setting, but also as a critique of how humans treat and behave to nature. The River, The River in March, The Jaguar, Hawk Roosting, To Paint A Water Lily, and Pike are Ted Hughes’ nature-themed poems. This article analyzes human behavior against nature using eco-criticism proposed by Cheryll Glotfelty and applies the concepts of animals and pollution by Greg Garrard as the principle in analyzing these poems. The researchers also reveal messages from the poems about the importance of human consciousness to preserve nature. The result of this study explains that it shows human violence against nature without thinking about its impact on life of people. The human treatment depicted in these poems that reflect human life and natural conditions in England in the 20th century, where many natural disasters and natural damages occurred as the result of human bad behavior against nature. Nature is part of the life of living things and humans are dependent on nature. Therefore, the condition of nature depends on how humans treat nature.